2007
DOI: 10.1111/j.1556-4029.2007.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant Death Scene Investigation and the Assessment of Potential Risk Factors for Asphyxia: A Review of 209 Sudden Unexpected Infant Deaths

Abstract: At the Wayne County Medical Examiner Office (WCMEO) in Detroit, Michigan, from 2001 to 2004, thorough scene investigations were performed on 209 sudden and unexpected infant deaths, ages 3 days to 12 months. The 209 cases were reviewed to assess the position of the infant at the time of discovery and identify potential risk factors for asphyxia including bed sharing, witnessed overlay, wedging, strangulation, prone position, obstruction of the nose and mouth, coverage of the head by bedding and sleeping on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 22 publications
7
59
2
1
Order By: Relevance
“…Research have shown conclusively that death scene investigation may assist in identifying underlying risk factors for SIDS and can also identify cases of wedging or accidental suffocation/strangulation which cannot be proved at post mortem examination [8,14]. This is important even if the infant was removed from the scene of death and resuscitated or rushed to hospital, as is often the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research have shown conclusively that death scene investigation may assist in identifying underlying risk factors for SIDS and can also identify cases of wedging or accidental suffocation/strangulation which cannot be proved at post mortem examination [8,14]. This is important even if the infant was removed from the scene of death and resuscitated or rushed to hospital, as is often the case.…”
Section: Discussionmentioning
confidence: 99%
“…The value of death scene investigation is important in determining risk factors for SIDS [7,8]. Death scene investigation may also elucidate the mechanism of death in some instances, which includes accidental suffocation and wedging [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sleeping on the side with one' s face against the back cushions of the sofa or against another person can result in suffocation. 27 Past analyses have found that infant deaths on sofas are usually asphyxia deaths from entrapment between a person and the sofa cushions, overlay by another person, or wedging against the sofa cushions. 18,28,29 Indeed, the cause of death for infants on sofas in this sample was most frequently classified as ASSB rather than SIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Shapiro-Mendoza et al, 3 in a more recent study using a combination of data similar to the data sources in our study, including medical examiner, law enforcement, and hospital records, revealed that 47.9% of deaths were attributed by the medical examiner to ASSB. 4 Even the article cited by Dr Cutz (Pasquale-Styles et al 5 ) revealed that "if the witnessed overlays, entrapments, strangulations and infants found with their noses and mouths blocked and/ or their heads covered represent asphyxia deaths, then a minimum of 108 (51.7%) in this study died of asphyxia" and "this would represent a conservative estimate of asphyxia deaths, as it does not take into account infants who died in high-risk sleep situations." 5 Dr Cutz also found implausible the proposed mechanism of suffocation of the older age group, stating that "actual scene reconstruction studies are often inconclusive" and citing Pasquale-Styles et al 5 We disagree with this conclusion; again, Pasquale-Styles et al 5 found that over half of the infant deaths in that study demonstrated a clear asphyxia mechanism.…”
mentioning
confidence: 99%
“…4 Even the article cited by Dr Cutz (Pasquale-Styles et al 5 ) revealed that "if the witnessed overlays, entrapments, strangulations and infants found with their noses and mouths blocked and/ or their heads covered represent asphyxia deaths, then a minimum of 108 (51.7%) in this study died of asphyxia" and "this would represent a conservative estimate of asphyxia deaths, as it does not take into account infants who died in high-risk sleep situations." 5 Dr Cutz also found implausible the proposed mechanism of suffocation of the older age group, stating that "actual scene reconstruction studies are often inconclusive" and citing Pasquale-Styles et al 5 We disagree with this conclusion; again, Pasquale-Styles et al 5 found that over half of the infant deaths in that study demonstrated a clear asphyxia mechanism. 5 Finally, Dr Cutz expressed concern that our study and other recent studies "create the impression that the cause of sudden unexpected infant death including sudden infant death syndrome (SIDS) has now been identified and a simple solution exists to prevent such death," thereby implying that further research into molecular and genetic etiologies to sleep-related infant deaths is unnecessary.…”
mentioning
confidence: 99%